PENGGUNAAN ALAT RETORIS NAJWA SHIHAB DALAM KANAL YOUTUBE DENNY SUMARGO - Hesti, Hesti; Hindun, Hindun; Oktiana, Regita; Aulianto, Mutiara (Universitas Negeri Makassar, 2024)
This research aims to highlight the language style used by Najwa Shihab, especially the theory of comparative majas. The data in this study are some of Najwa Shihab's utterances that use rhetorical devices in expressing ideas, ideas, and facts, and the data source of this study is Denny Sumargo's Podcast with Najwa Shihab entitled ‘Najwa Shihab Maju CAPRES in 2024!?’ uploaded on Denny Sumargo's YouTube channel on 15 December 2022. Now Indonesia is in a crisis of criticism!!’ uploaded on Denny Sumargo's YouTube channel on 15 December 2022. The research data collection used listening and recording techniques because the researcher did it through Podcasts on Denny Sumargo's YouTube channel. The data analysis technique in this research uses descriptive qualitative techniques. The results of the analysis show that Najwa Shihab tends to use metaphor, analogy, and hyperbole in discussing political issues in Indonesia. The video found the use of comparison, metaphor, analogy, and hyperbole.